Recent Advances and the Prospect of Hypervalent Iodine Chemistry - Yang, Xiao-Guang; Hu, Ze-Nan; Jia, Meng-Cheng; Du, Feng-Huan; Zhang, Chi (Synlett, 2021)
Nowadays, hypervalent iodine chemistry has remarkably advanced in parallel with the emergence of novel hypervalent iodine reagents. Hypervalent iodine reagents, due to their outstanding characteristics including rich reactivities, excellent chemoselectivity, stability, and environmental friendliness, are becoming more and more popular in the synthetic organic chemistry. In this Account, a number of recent elegant research works and our perspective on the future of hypervalent iodine chemistry is presented.1 Introduction2 Recent Advances and Discussion2.1 Novel Reactivities of Hypervalent Iodine Reagents2.2 Atom-Economical Reactions Promoted by Hypervalent Iodine Reagents2.3 Other Applications of Hypervalent Iodine Reagents2.4 The Applications of DFT Calculations in Elucidating Reaction Mechanism Involving Hypervalent Iodine Reagents3 Outlook and Conclusion
Keywords: hypervalent iodine; oxidation; functional group transfer; atom economy; DFT calculation